Black hole solutions for scale-dependent couplings: the de Sitter and the Reissner–Nordström case. (6th January 2016) - Koch, Benjamin; Rioseco, Paola
Abstract: Allowing for scale dependence of the gravitational couplings leads to a generalization of the corresponding field equations. In this work, these equations are solved for the Einstein–Hilbert and the Einstein–Maxwell case, leading to generalizations of the (Anti)-de Sitter and the Reissner–Nordström black holes. These solutions are discussed and compared to their classical counterparts.